PENDAMPINGAN KEGIATAN MENDONGENG SEBAGAI UPAYA MENSTIMULASI KEMAMPUAN LITERASI ANAK USIA DINI - Siregar, Masyunita; Sherly Utami, Winda (Pendidikan Sejarah FKIP Universitas JAMBI, 2023)
Literacy plays an important role in early childhood language development. The purpose of this service is to provide storytelling activity assistance to PAUD teachers to stimulate early childhood literacy skills. This service uses lecture, discussion-information and evaluation methods. The result of this service activity is that the storytelling ability of PAUD or kindergarten teachers who take part in the activity is getting better. It can be seen from the use of interactive media and the ability to imitate the character's voice in the story that is increasingly pariative. So that the literacy skills of students are increasing.